Effectiveness of Canva-Based Interactive Learning Media Using Problem-Based Learning to Improve Creative Thinking Skills on Balancing Redox Reactions - Halimatus Sakdhiah; Muhammad Hasan; Sri Winarni; Muhamad Aditya Hidayah (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The unavailability of valid learning media causes the lack of improvement in learning outcomes. The study aims to develop Canva-based interactive learning media using the problem-based learning (PBL) approach to improve students’ learning outcomes and creative thinking skills (CTS) on redox reaction material. The research employed the research and development (R&D) method with the ADDIE model. The subjects of the study were twelfth-grade students of SMA Negeri 2 Timang Gajah, divided into two classes: the experimental class (n=24) and the control class (n=21). Data collection instruments consisted of expert validation sheets, student response questionnaires, posttest questions, and observation sheets. Data analysis used Aiken’s V validity test, Shapiro-Wilk normality test, and paired sample t-test. The results of media expert validation showed an average feasibility of 80.70% (valid category), while material expert validation reached 95.37% (very valid). Student responses to the media showed a score of 88.8% (very positive). The average posttest score of learning outcomes in the experimental class (81.25) was significantly higher than that of the control class (50.52). Students’ CTS in the experimental class also showed improvement across all indicators (fluency 87.5; flexibility 84.3; originality 72.9; elaboration 58.3), with the average observation score of CTS reaching 80.7% (high category). The developed Canva-based interactive learning media using the PBL approach was proven to be valid, practical, and effective in improving students’ learning outcomes and CTS on balancing redox reactions